NAFLD in the Absence of Metabolic Syndrome: Different Epidemiology, Pathogenetic Mechanisms, Risk Factors for Disease Progression? - Yilmaz, Yusuf (Seminars in Liver Disease, 2012)
Metabolic syndrome (MetS) is a cluster of metabolic abnormalities that have been associated with an increased risk of developing nonalcoholic fatty liver disease (NAFLD). Insulin resistance and central obesity are the key components of MetS, ultimately leading to liver fat accumulation and the subsequent development of necroinflammatory liver injury. However, the origin and nature of the metabolic stressors responsible for stimulating the progression of simple steatosis to nonalcoholic steatohepatitis (NASH) remain to be clearly identified. In addition, epidemiologic research on the association between MetS and NAFLD has provided only limited information to guide the development of targeted interventions, in particular, nutrition and pharmacologic prevention programs. This review summarizes the evidence supporting the proposal that NAFLD is not invariably associated with the presence of MetS, and mechanisms other than insulin resistance may contribute to the chronic inflammatory processes that underpin the development of liver fat accumulation and the subsequent architectural distortion of the liver. A special focus is given to increased hemoglobin as a risk factor for the development of NAFLD in the absence of MetS.
Keywords: nonalcoholic fatty liver disease; metabolic syndrome; risk factors; hemoglobin